Determination of Aldosterone Hormone and Alpa Feto-Protein Concentrations in Normal Pregnant Women and in Pregnancy Induced Hypertension - Waser S. Khlaf; Mossa M. Marbut (Journal of Madenat Alelem University College, 2020)
This study was conducted in the Department of Life Sciences, Balad Hospital, to see some physiological changes to high blood pressure Pregnancy by estimating hormone concentration and Aldosterone. The statistical results of the study showed a significant increase in both hormone (P <0.01) and the same was observed for urea concentrations observed. A significant increase at a significant level (P <0.01)) and this moral increase is in pregnant women with high blood pressure compared to pregnant women with blood pressure. The variables that did not notice a significant difference among pregnant women Hypertension compared to the control group, no difference was observed In creatinine results.